Lactate Dehydrogenase B and Pyruvate Oxidation Pathway Associated With Carfilzomib-Related Cardiotoxicity in Multiple Myeloma Patients: Result of a Multi-Omics Integrative Analysis - Tantawy, Marwa; Chekka, Lakshmi Manasa; Huang, Yimei; Garrett, Timothy J.; Singh, Sonal; Shah, Chintan P.; Cornell, Robert F.; Baz, Rachid C.; Fradley, Michael G.; Waheed, Nida; DeRemer, David L.; Yuan, Lihui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Multiple myeloma (MM) is the second most frequent hematologic cancer in the United States. Carfilzomib (CFZ), an irreversible proteasome inhibitor being used to treat relapsed and refractory MM, has been associated with cardiotoxicity, including heart failure. We hypothesized that a multi-omics approach integrating data from different omics would provide insights into the mechanisms of CFZ-related cardiovascular adverse events (CVAEs). Plasma samples were collected from 13 MM patients treated with CFZ (including 7 with CVAEs and 6 with no CVAEs) at the University of Florida Health Cancer Center. These samples were evaluated in global metabolomic profiling, global proteomic profiling, and microRNA (miRNA) profiling. Integrative pathway analysis was performed to identify genes and pathways differentially expressed between patients with and without CVAEs. The proteomics analysis identified the up-regulation of lactate dehydrogenase B (LDHB) [fold change (FC) = 8.2, p = 0.01] in patients who experienced CVAEs. The metabolomics analysis identified lower plasma abundance of pyruvate (FC = 0.16, p = 0.0004) and higher abundance of lactate (FC = 2.4, p = 0.0001) in patients with CVAEs. Differential expression analysis of miRNAs profiling identified mir-146b to be up-regulatein (FC = 14, p = 0.046) in patients with CVAE. Pathway analysis suggested that the pyruvate fermentation to lactate pathway is associated with CFZ-CVAEs. In this pilot multi-omics integrative analysis, we observed the down-regulation of pyruvate and up-regulation of LDHB among patients who experienced CVAEs, suggesting the importance of the pyruvate oxidation pathway associated with mitochondrial dysfunction. Validation and further investigation in a larger independent cohort are warranted to better understand the mechanisms of CFZ-CVAEs.